Multi-frequency observations and spectral analysis of two gigahertz-peaked spectra pulsars. Issue 2 (10th July 2018) - Rożko, K; Rajwade, K M; Lewandowski, W; Basu, R; Kijak, J; Lorimer, D R
ABSTRACT: We report the multi-frequency observations of two pulsars: J1740+1000 and B1800−21, using the Giant Metrewave Radio Telescope and the Green Bank Telescope . The main aim of these observations was to estimate the flux-density spectrum of these pulsars, as both of them were previously reported to exhibit gigahertz-peaked spectra. J1740+1000 is a young pulsar far from the Galactic plane and the interpretation of its spectrum was inconclusive in the light of the recent flux-density measurements. Our result supports the gigahertz-peaked interpretation of the PSR J1740+1000 spectrum. B1800−21 is a Vela-like pulsar near the W30 complex, whose spectrum exhibited a significant change between 2012 and 2014. Our analysis shows that the current shape of the spectrum is similar to that observed before 2009 and confirms that the observed spectral change happens on a time-scale of a few years.